Female Labour Migration as a Factor of Social Changes - ФетисоваЕвгения Николаевна (Journal of Economic Sociology, 2010)
The work of Russian women as hostesses in the night clubs in North-East Asia is the legal business that leads to the illegal activities (sex-services), which relate to the shadow economy. Those girls experienced in hostess plus prostitution strategy face the transformation of values, they come back to Russia with changed psychics as they are sure that under the certain conditions prostitution is the usual type of work like seller or bookkeeper. Such experience in labour migration transforms the women world outlook by changing their moral and ethics, psychological norms and rules of behavior. It means that we face institutional changes here. The advantages of the job of hostess are also under focus. Being holders of changed social conciseness and at the same time successful socio-economic strategy the women-migrants transform gender stereotypes and make the role structure of the society be more difficult.